Excursion as a Motivational Learning Method for Slovenian as a Second and Foreign (As Well as First) Language - Valh Lopert, Alenka; Tatjana Vučajnk, Tatjana Vučajnk (Slavistična prepletanja 6, 2025)
The experiential learning method, which we present in this paper as a successful example of higher education pedagogical practice, is especially important for students learning Slovenian as a second or foreign language (also for learning a first language/mother tongue) because it gives them a foundation for learning, consolidating, and generally experiencing and familiarizing themselves with the use of Slovenian in the real world. Contemporary higher education teaching and pedagogical practice consolidate and combine both, i.e., linguistic (written and oral communication, translation, etc.) and intercultural (cuisine, cultural heritage, history, etc.) competences. This could be achieved by introducing the excursion method as experiential learning based on cross-border inter-university cooperation (in this case between Klagenfurt and Maribor).